Identities, politics, and rights - Sarat, Austin; Kearns, Thomas R. (Amherst series in law, jurisprudence, and social thought., 1997)
The subject of rights occupies a central place in liberal political thought. This tradition posits that rights are entitlements of individuals by virtue of their personhood and that rights stand apart from politics, that rights in fact hold at bay intrusions of state policy. The essays in Identities, Politics, and Rights question these assumptions and examine how rights constitute us as subjects and are, at the same time, implicated in political struggles. In contrast to the liberal notion of rights' universality, these essays emphasize the context-specific nature of rights as well as their constitutive effects.